Atezolizumab in patients with advanced non-small cell lung cancer and history of asymptomatic, treated brain metastases: Exploratory analyses of the phase III OAK study. (February 2019) - Gadgeel, Shirish M.; Lukas, Rimas V.; Goldschmidt, Jerome; Conkling, Paul; Park, Keunchil; Cortinovis, Diego; de Marinis, Filippo; Rittmeyer, Achim; Patel, Jyoti D.; von Pawel, Joachim; O'Hear, Carol; Lai, Catherine; et al.
Highlights: Compared with docetaxel in patients who had a history of treated brain metastases. Atezolizumab had an acceptable neurologic safety profile. Atezolizumab showed a trend toward overall survival benefit. Atezolizumab prolonged time to identification of new symptomatic brain lesions. Abstract: Objectives: To assess the safety and efficacy of atezolizumab and docetaxel in patients with and without a history of asymptomatic, treated brain metastases in the phase III OAK trial. Materials and methods: Patients received 1200 mg atezolizumab or 75 mg/m 2 docetaxel every 3 weeks until unacceptable toxicity, disease progression, or loss of clinical atezolizumab benefit. Patients with asymptomatic, treated supratentorial metastases were eligible. Patients had brain scans before enrollment; follow-up brain scans and treatment were required when clinically indicated. Results: Approximately 14% of patients in each arm had a history of asymptomatic, treated brain metastases (61/425 in the atezolizumab arm and 62/425 in the docetaxel arm). Fewer treatment-related adverse events (AEs), serious AEs, and treatment-related neurologic AEs were reported with atezolizumab than with docetaxel, regardless of history of asymptomatic, treated brain metastases. In patients with a history of asymptomatic, treated brain metastases, median overall survival (OS) was longer with atezolizumab than with docetaxel (16.0 vs 11.9 months; hazard ratio = 0.74; 95% CI: 0.49–1.13). Median OS was also longer with atezolizumab in patients without a history of asymptomatic, treated brain metastases (13.2 vs 9.3 months; hazard ratio = 0.74; 95% CI: 0.63–0.88). Landmark analyses showed that patients with a history of asymptomatic, treated brain metastases had a lower probability of developing new symptomatic brain lesions with atezolizumab vs docetaxel at 6–24 months. Patients without a history had a lower probability with atezolizumab at 18–24+ months. Conclusion: Atezolizumab had an acceptable neurologic safety profile, showed a trend toward an OS benefit, and led to a prolonged time to radiographic identification of new symptomatic brain lesions compared with docetaxel in patients who had a history of asymptomatic, treated brain metastases. Clinicaltrials.gov registration number: NCT02008227.